Faktor-Faktor yang Berhubungan dengan Depresi pada Ibu Postpartum di Kota Yogyakarta - Priyani Haryanti; Reni Puspitasari (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Background: Postpartum mothers would experience uterine involution and the function return to normal after six weeks. Mood disorders was difficult to detect, the psychological change in postpartum mother untreated could be postpartum depression (PPD). Methods: This research used correlation with cross-sectional design. The population of post-partum mothers in Yogyakarta Primary Health Care, with average was 60 labor/month. Sampling technic used non probability sampling with a quota of 90 postpartum mothers. The instruments were respondent characteristic: age, family income, parity, other instruments: method of delivery, status of residence, multidimensional scale of perceived social support (MSPSS), Roosenberg Self Esteem Scale (RSES), and Endiburg Postpartum Depression (EPDS). Descriptive analysis was frequency distribution, bivariate Chi-square and multivariate logistic regression. Results: There was the relationship between family support and self-esteem with postpartum depression with p-value